A cross-sectional study on the moderating effect of self-efficacy on the relationship between sociodemographic variables and nutrition literacy among older adults in rural areas of North Sichuan - Liu, Shasha; Fan, Xiaomei; Jiang, Li; Liu, Tao (Frontiers in Nutrition, 2024)
Objective The purpose of this study is to examine the moderating role of self-efficacy among rural elderly individuals in northern Sichuan Province in the relationship between certain sociodemographic variables and nutritional literacy. Methods Convenience sampling was used to select 264 elderly individuals aged 60 and above from rural communities in Cangxi County, Guangyuan City, Yilong County, Nanchong City, and Bazhou District, Bazhong City, Sichuan Province. A self-designed questionnaire, including sociodemographic variables, the General Self-Efficacy Scale (GSES), and the Nutrition Literacy Questionnaire for the Elderly (NLQ-E), was administered through face-to-face interviews using a paper-based version. The relationships between sociodemographic variables, self-efficacy, and nutritional literacy in the elderly were analyzed using SPSS 26.0 and the Process plugin to examine the relationships between variables and to test for moderation effects. Results (1) There were significant differences in nutrition literacy scores among elderly people of different ages, genders, marital statuses, educational levels, personal monthly living expenses, dental conditions, and number of chronic diseases (p < 0.05). (2) When elderly individuals have lower self-efficacy, their nutritional literacy is lower as they become older, and they have poorer nutritional literacy with a higher number of chronic diseases. Conclusion General population demographic data has a significant impact on the nutritional literacy level of elderly people in rural areas of northern Sichuan. Self-efficacy plays a moderating role in the relationship between age and nutritional literacy, as well as the relationship between the number of chronic diseases and nutritional literacy.